The Magic Sauce: Practices of Facilitation in Online Policy Deliberation - Dmitry Epstein; Gilly Leshed (Journal of Deliberative Democracy)
Online engagement in policy deliberation is one of the more complex aspects of open government. Previous research on human facilitation of policy deliberation has focused primarily on the citizens who need facilitation. In this paper we unpack the facilitation practices from the perspective of the moderator. We present an interview study of facilitators in RegulationRoom – an online policy deliberation platform. Our findings reveal that facilitators focus primarily on two broad activities: managing the stream of comments and interacting with comments and commenters – both aimed at obtaining high quality public input into the particular policymaking process. Managing the immediate goals of online policy deliberations, however, might overshadow long-term goals pf public deliberation, i.e. helping individuals develop participatory literacy beyond a single policy engagement. Our contribution is twofold: we unpack the practice of human facilitation in online policy deliberation, and suggest both design and process implications for sustainable growth of civic engagement environments beyond the individual case we analyze.